Obstacles to Provision of Protection for Victims of Sexual Violence - Sri Novita A. Gobel (Estudiante Law Journal, 2026)
The purpose of this research is to know and analyze about how to protect the rights of children who are victims of pedophilia. This research was conducted at the Social Service for the Empowerment of Women and Children. This writing is done by interviewing officers and collecting data in the agency. The results of this study indicate that the provision of protection for the rights of child victims of pedophilia crimes has not run optimally. This is due to internal and external factors. of pedophilia. The external factor is that not all witnesses or victims' families want to receive psychosocial assistance because of the embarrassment caused by what happened to the victim's child.